Improvements in energy efficiency and the potential use of hydrogen fuel cells in railway transport - Boris M. Lapidus (Вестник Научно-исследовательского института железнодорожного транспорта, 2019)
This article presents the value of further increase of the energy efficiency in railway transport in combination with transition to the non-standard sources of energy. This is done within the paradigm of sustainable development and decarbonization in the global economy and by also taking into account the objectives stated in the document “Global perspective of railway transport development until 2050.” Hydrogen fuel cells, which are being studied by the Technical and Scientific Council of the JSC “RZD”, have demonstrated to be the most beneficial. The global trends of commercial use of fuel cells for transport are based on the unique properties of hydrogen as a fuel: high energy efficiency, ecological safety, and capability to be used without electric grids. Taking into account technological and ecological value, the transition from diesel traction to hydrogen fuel cell traction is justified and can be evaluated as a step of evolution that is as valuable as the transition from steam traction to diesel traction. Empirical proof is available that hydrogen is not hazardous to handle with properly designed equipment. The potential of the Russian science allows fulfilling appropriate research and development. We have taken into account that the required scientific and technological competences are available in different scientific centers and their effective integration is required. The conclusion states that the required conditions exist for introduction of the hydrogen fuel cells to the rolling stock in Russia. Although manufacturing of the critical fuel cells is not currently available in the Russian Federation, it can be arranged if demand is sufficient. This will require the collaboration of customers and scientific investigators in the project development of electric rolling stock in which hydrogen fuel cells can be used.